Mouse in space! - Barbieri, Francesco, 1970-; Aliprandi, Christian (New York : Scholastic, 2013)
Geronimo Stilton is called upon by the authorities to thwart the plans of an evil professor and travels on a top secret mission to outer space.
Translation of: S.O.S. C'e un topo nello spazio!
"Geronimo Stilton."
4.5
3-6
Keywords: Stilton, Geronimo (Fictitious character) -- Juvenile fiction; Mice -- Juvenile fiction; Space flight -- Juvenile fiction; Stilton, Geronimo (Fictitious character) -- Fiction; Mice -- Fiction; Space flight -- Fiction; Stilton, Geronimo (Fictional character) -- Fiction; Mice -- Fiction; Space flight -- Fiction